AXL/Gas6 signaling mechanisms in the hypothalamic-pituitary-gonadal axis - Mohammadzadeh, Pardis; Amberg, Gregory C. (Frontiers in Endocrinology, 2023)
AXL is a receptor tyrosine kinase commonly associated with a variety of human cancers. Along with its ligand Gas6 (growth arrest-specific protein 6), AXL is emerging as an important regulator of neuroendocrine development and function. AXL signaling in response to Gas6 binding impacts neuroendocrine structure and function at the level of the brain, pituitary, and gonads. During development, AXL has been identified as an upstream inhibitor of gonadotropin receptor hormone (GnRH) production and also plays a key role in the migration of GnRH neurons from the olfactory placode to the forebrain. AXL is implicated in reproductive diseases including some forms of idiopathic hypogonadotropic hypogonadism and evidence suggests that AXL is required for normal spermatogenesis. Here, we highlight research describing AXL/Gas6 signaling mechanisms with a focus on the molecular pathways related to neuroendocrine function in health and disease. In doing so, we aim to present a concise account of known AXL/Gas6 signaling mechanisms to identify current knowledge gaps and inspire future research.